FAKTOR DETERMINAN PEMANFAATAN LAHAN TIDUR DI KECAMATAN TEON NILA SERUA (TNS) MALUKU TENGAH: SEBUAH ANALISIS REGRESI - Penina T. Istia; Juvrianto Chrissunday Jakob (University of Jember, 2021)
The people in TNS sub-district are the evacuation areas of 16 villages from the Teon Nila Serua Island, where each household is given an area of two hectares or 20.000 m2 to be managed into agricultural land and settlements. The total area of TNS sub-district is 24.208 km2 with a population of 14,354 people, and area of idle land is 290 hectares. The problem of this research is what factors affect the use of idle land in TNS District, Central Maluku. The method used in data collection is interview and questionnaire which are given to productive farmers during the Covid-19 pandemic as interviewee, while the data analysis method using multiple linear regression with the results obtained. The dummy variables of farmer profession, capital, technology and the dummy of the division of labor have a positive effect on the use of idle land during the Covid 19 pandemic, in TNS sub-district, Central Maluku. Beside that, the use of idle land and production yields is increased from before.